Cultural Factors and Women SMEs Performance - Sangu, Deogratius (International Journal of Business, Law, and Education, 2025)
This study explores the impact of cultural factors on the performance of women-owned SMEs in Tanzania. cultural factors such as gender norms, family roles, education, and societal expectations are investigated to shape the entrepreneurial success of women. The study reviewed 45 articles from the five major academic databases which are: Google Scholar, Emerald, Taylor and Francis, Elsevier/Science Direct, and Sage. The Google Scholar database contributed the highest number, with 30 articles selected. Emerald Insights, Elsevier Science Direct, and Sage contributed 4 articles per each database, and lastly, Taylor & Francis provided the study with 3 articles ranging from 1997 to 2024. The articles were collected in diverse regions, from developed to developing countries. The study suggests that cultural barriers like immobility, poor societal support, and ethnic influences negatively affect the performance of women SMEs. At the same time, family roles, education, and role models foster growth. Future research should explore how cultural factors interact with economic and technological forces and the role of government interventions in reducing cultural hindrances. This Study contributes to the knowledge on how cultural factors can both hinder and promote women's business economic and financial situations.